Dancing the Ritual on the Kūṭiyāṭṭam Theatre Stage - Virginie Johan (Ksiegarnia Akademicka Publishing, 2017)
Until the 1960s, Kūṭiyāṭṭam**—India’s Sanskrit theatre—was exclusively performed in Hindu temples of Kerala by an ensemble of three ritual performers of high status: the Cākyār actor-master, the Nampyār percussionist, and the Naṅṅyār reciter, cymbalist and actress. Within this devotional context, Kūṭiyāṭṭam, whose essence is theatre (nāṭya), is considered an offering of ‘dance’ (nṛtta) to the main divinity. Furthermore, the performative cycles, lasting from three to forty-one days, incorporate dances known as ‘kriya’, literally ‘what has to be done’ or ‘action’, designating the ritual action here. This paper attempts to complement previous studies based on the Indian theory of theatre, by questioning the uses and roles of dance in the Kūṭiyāṭṭam theatrical sphere and tackling the issue of boundaries between dance and dramatic action. The study draws on long-range anthropological research as well as on the Kūṭiyāṭṭam literature, especially the Cākyar’s acting and production manuals (āṭṭaprakāram and kramadīpikā) written in Malayalam, three of which are composed for the performance of the following Sanskrit plays: Bālacaritam and Abhiṣekanāṭakam of Bhāsa, and Āścaryacūḍāmaṇi of Śaktibhadra.